All It Takes for Corruption in Health Systems to Triumph, Is Good People Who Do Nothing; Comment on "We Need to Talk About Corruption in Health Systems" - Saskia Mostert; Gertjan Kaspers (Kerman University of Medical Sciences, 2019)
Numerous investigations demonstrate that the problem of corruption in the health sector is enormous and has grave negative consequences for patients. Nevertheless, the problem of corruption in health systems is far from eminent in the international health policy debate. Hutchinson, Balabanova, and McKee have identifed in their Editorial five reasons why the health policy community has been reluctant to talk about it: (1) Problem of defining corruption; (2) Some corrupt practices are actually ways of making dysfunctional systems work; (3) The serious challenges to researching corruption; (4) Concerns that focus on corruption is a form of victim blaming that ignores larger issues; and (5) Lack of evidence about what works to tackle it. In this commentary, we pay a closer and critical look at these five excuses for doing nothing. We conclude that the vast majority of the world population, being the poor in low and middle-income countries (LMICs) who disproportionately suffer from the problem of corruption in health systems, need good people with high moral and ethical principles who have the courage to disregard these five reasons. The poor need good people who understand that it is crucial to first acknowledge this problem, despite the obvious uncertainties involved, before you can change it. The poor therefore need good editors, good policy-makers, good managers, and good clinicians. We agree with the authors that we first need to talk about corruption. But above all, we need good people who are subsequently willing to walk the talk.